Reserva do possível como uma estratégia jurídica para restringir o direito à saúde: o argumento da "reserva do possível" na jurisprudência do Supremo Tribunal Federal - Santos, Charlston Ricardo Vasconcelos dos (2015)
The present dissertation hás as object of study the Theory of Possible Reserve as legal strategy of the State to restrict, from the Federal Constitution of Brazil of 1988, the fundamental right to health in the deal taken to the judiciary. The Theory of the Reservation possible, extracted from a decision given of the German Federal Constitutional Court, known as numerus clausus, hás been raised by the State, in Brazil, at the moment when he is added for effect the right to health on behalf of individual, the collective or society. The overall objective of this study is to verify if the fundamentais of this German decision also serve for the Brazilian State support the theory of Possible reservation against the fundamental right to health. As a specific objective, the aim is to identify if the Supreme Federal Court (STF) accepts this theory on this fundamental right as well as what are the requirements, conditions, circumstances and reasons that leading to accept or not this theory. The present work whether justified because, although there are doctrinal studies on the theory of Possible reservation, not found the presence of doctrine which investigate the foundations of German decision are able to impose this theory to the fundamental right to health in Brazil; also not located to investigate the requirements, conditions, circumstances and reasons that lead the STF to admit or not the possible reservation on the fundamental right to health. Another factor that justifies this research is the considerable increase of judicial demands involving this right and this theory against legal insecurity that establishes when the State is called upon to implement this right and he claims that it is bounded by booking possible. It was used as a methodology for this dissertation bibliographic search and Boolean. The bibliographical allowed an analysis of doctrine about human rights; fundamental rights; social rights; existential minimum; no social backlash; public policies; separation of powers; judicialization of public policies; booking possible; public budget and burden of proof. The Boolean search, as base on the search for key expressions in the jurisprudence of the STF, enabled the documentary research of the decisions of the STF and the empirical research, which allowed identified the position of the STF when judges cases involving both the fundamental right to health and the possible reservation. As well as methodology, we used the bardiniana content analysis to analyze the fundamentais of the German decision, as well as to investigate what are the requirements, conditions, circumstances and reasons that led the STF to accept or not the theory of possible Reserve facing the fundamental right to health. As results, the content analysis of the German decision allowed deduce that the fundamentais of this decision not allow that the State maintains the reservation possible as bounding of the right to health, unless adapted to current fundamentais. The empirical research on the position of the STF hás identified that he admits the Possible Reservation if the State proved a fair reason for the delimitation of the fundamental right to health.